Number 27 (March 1993) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1993)
(March 1993) - A Status Survey of the Western Sand Darter, Ammocrypta clara, in the Big Black River, Mississippi. By F. Pezold, et al., 5 pp. Museum Notes by B.M. Burr and M.L. Warren, 3 pp. Minutes, Regional Reports and Announcements.
Keywords: western sand darter; ammocrypta clara; big black river; mississippi